Antimicrobial Peptides Controlling Resistant Bacteria in Animal Production - Rodrigues, Gisele; Souza Santos, Lucas; Franco, Octávio Luiz (Frontiers in Microbiology, 2022)
In the last decades, antimicrobial resistance (AMR) has been a worldwide concern. The excessive use of antibiotics affects animal and human health. In the last years, livestock production has been used antibiotics as food supplementation. This massive use can be considered a principal factor in the accelerated development of genetic modifications in bacteria. These modifications are responsible for antimicrobial resistance (AMR), can be widespread to pathogenic and commensal bacteria. In addition, these antibiotics residues can be dispersed by water and sewer water system, the contamination of soil and, water and plants, in addition, can be stocked in tissues such as muscle, milk, eggs, fat, and others. These residues can be spread to humans by the consumption of water or contaminated food. In addition, studies have demonstrated that antimicrobial resistance may be developed by vertical and horizontal gene transfer, producing a risk to public health. Hence, the World Health Organization (WHO) in 2000 forbid the use of antibiotics for feed supplementation in livestock. In this context, to obtain safe food production, one of the potential substitutes for traditional antibiotics is the use of antimicrobial peptides (AMPs). In general, AMPs present anti-infective activity, and in some cases immune response. A limited number of AMP-based drugs are now available for use in animals and humans. This use is still not widespread due to a few problems like in-vivo effectiveness, stability, and high cost of production. This review will elucidate the different AMPs applications in animal diets, in an effort to generate safe food and control AMR.